Strategies to improve High Andean rangelands - Lima Molina, Nila (2020)
A field study was conducted to evaluate the impact of phosphorous fertilization and the introduction of white clover (Trifolium repens) in native grasslands dominated by Festuca dolichophylla (festuca). The study area was located at 4500 m of altitude in the Ayaracra sector, Pasco region, which corresponds to the Puna ecoregion of Peru. The experimental design was a 2x2x5 factorial in blocks with two levels of phosphorus (0 and 80 kg/ha), two distances between clump seeding gaps (0.5 and 1.0 m) and five climatic seasons. Plant height, foliar expansion, vigor (volume, height), plant weight (g/m2), number of flowering heads (inflorescences), degree of nodulation, nitrogen content in the leaves and stems of fescue were evaluated and nitrogen content in the soil where white clover was present. Phosphorus fertilization (80 kg/ha) and planting spacing (0.5 cm) showed a significant effect on the clover height, foliar expansion and degree of nodulation. In F. dolichophylla, phosphorous fertilization showed a significant improvement in plant volume and height, planting spacing of 0.5 cm improved the number of inflorescences and spacing at 1 m improved height. Precipitation (during the rain peak) favored the response of foliar expansion and plant height.